Minha voz, minha vida: minhas experiências vocais dentro e fora da academia - LACERDA, Sérgio Aloyzio da Silva (2021)
This final paper is a research, that aims at analyzing, through my memories, the creation procedures of some characters that I have played since I started the theatrical practice, 1992, until the 2004 presentation, when I was accepted into the academy (ETDUFPA). It is divided in two parts; first, I analyze my creation procedures in some amateur theater groups, how the creation processes of my characters happened, taking into consideration mainly the step that works the creation of a vocal score not having an specific professional from the vocal area as a support for that moment; in the other part of my research, I analyze the procedures that I have developed in the academy, with a vocal coach, Walter Bandeira, available for that purpose. I make a comparison between the procedures adopted outside and within my graduation course; I highlight the importance of working with vocal techniques that help giving a higher quality when representing a sensation conducted by voice having breathing as a support, primordial procedure to give live to the character. This way, this reaseach does not intend to create a new vocal technique, however, I see in it, i observe for a possible organicity of the respiratory process in favor of this vocal score required for the scene.